Validation of expression profiles of differentially expressed transcripts identified in cattle-derived and buffalo-derived Theileria parva isolates by RNA sequencing - Sibeko, K.P. (Kgomotso Penelope) (University of Pretoria, 2017)
Dissertation (MSc)--University of Pretoria, 2017.